Correlation between serum uric acid and thyroid function tests in patients with hypothyroidism - Tofique, Mahneem; Ansari, Masud Ali; Qamar, Khansa; Fatima, Fizza (International Journal of Pathology, 2025)
Background: Hypothyroidism has been associated with hyperuricemia due to reduced renal uric acid excretion. This study aimed to determine the correlation between serum uric acid and thyroid function tests in hypothyroid patients.Methods: This cross-sectional study was performed at the Department of Pathology, Nishtar Hospital Multan, from 22nd January to 21st July 2025. A total of 232 newly diagnosed hypothyroid patients aged 20-70 years were recruited through non-probability consecutive sampling. Individuals with renal, hepatic, or cardiovascular disease, or using anti-hypertensive or hypouricemic agents, were excluded. Serum uric acid and thyroid function tests were analyzed on Cobas c31 chemistry autoanalyzer under standard internal quality control protocols. Data were analyzed using SPSS version 25. Normality was evaluated by Shapiro-Wilk test. Correlation between uric acid and thyroid parameters was determined using Spearman's rho, with p<0.05 considered significant.Results: The median age of participants was 38 years (IQR: 27 to 49.75); 70.7% were female, and 51.3% of the participants were obese. Median serum uric acid, TSH, free T3, and free T4 values were 7.5 mg/dl, 14.05 mU/L 0.31 ng/dl and 0.51 ng/dl, respectively. Serum uric acid showed a strong positive correlation with TSH (rs=0.81, p <0.001) and strong negative correlations with free T3 (rs= –0.736, p <0.001) and free T4 (rs= –0.779, p <0.001). These correlations remain significant after stratification by age gender obesity and smoking status.Conclusion: Serum uric acid is positively correlated with TSH levels and negatively correlated with T3 and T4 in hypothyroid patients, suggesting that hyperuricemia may serve as a biochemical marker of disease severity and metabolic dysregulation in hypothyroidism.